HR+/Her2- breast cancer in pre-menopausal women: The impact of younger age on clinical characteristics at diagnosis, disease management and survival. (December 2016) - De Camargo Cancela, Marianna; Comber, Harry; Sharp, Linda
Highlights: Tumour size did not differ between age groups, but the percentage of nodal disease and high-grade tumours was higher in women aged 20–39 than women aged 40–49. Small, but significant differences in treatment were observed: the younger age-group (20–39) more often had mastectomy and chemotherapy compared to women aged 40–49. Age is an independent prognostic factor in younger women diagnosed with less aggressive subtypes, supporting the hypothesis that breast cancer in women under 40 is a more aggressive entity. Abstract: Young women (20–39 years-old) with breast cancer are diagnosed with more aggressive tumours and consequently have poorer survival. However, there is an evidence gap as to whether age has an independent effect on survival of pre-menopausal women diagnosed with HR+/Her2- tumours. The aim of this population-based study was to compare characteristics at diagnosis, determinants of treatment and survival in women aged 20–39 and 40–49 years diagnosed with HR+/Her2- tumours. From the National Cancer Registry Ireland, we identified women aged 20–49 diagnosed with a first invasive HR+/Her2- breast cancer during 2002–2008. Women aged 20–39 were compared to those aged 40–49 years. Poisson regression with robust error variance was used to explore the impact of age on treatment receipt. Associations between age and survival from all causes was investigated using Cox models. In multivariate models, women aged 20–39 significantly more often having no cancer-directed surgery (IRR = 1.49, 95%CI 1.07, 2.08). In those having surgery, younger age was associated with significantly higher likelihood of receiving chemotherapy; age was not associated with receipt of adjuvant radiotherapy or endocrine therapy. Women aged 20–39 undergoing surgery were significantly more likely to die than women aged 40–49 (HR = 1.84, 95%CI: 1.31, 2.59). Age is an independent prognostic factor in younger women diagnosed with HR+/Her2- breast cancer, supporting the hypothesis that breast cancer in women under 40 has more aggressive behaviour, even within HR+/Her2- tumours. Future research should explore the reasons for poorer survival in order to inform strategies to improve outcomes in this age group.